2019
DOI: 10.2460/ajvr.80.12.1107
|View full text |Cite
|
Sign up to set email alerts
|

Histologic assessment of age-related changes in the temporomandibular joints of horses

Abstract: OBJECTIVE To describe histologic changes in the temporomandibular joints (TMJs) of horses of various ages. SAMPLE 22 TMJs from cadavers of 11 horses. PROCEDURES Horses were categorized into 3 age groups (group 1, 2 to 10 years old [n = 3]; group 2, 11 to 20 years old [3]; and group 3, > 20 years old [5]). Each TMJ was sectioned into 5-mm slices, preserved in formalin, decalcified in formic acid, and routinely processed for histologic analysis. Joints were systematically assessed by use of previously des… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 30 publications
1
8
0
Order By: Relevance
“…The hyaline cartilage contained many hypertrophied chondrocytes and relatively small foci of necrosis. The deep layers of the hyaline cartilage were undergoing endochondral ossification, as expected in a horse less than 2 years old (Smyth et al, 2019). There was a relatively large depression in the lateral aspect of the articular surface of the mandibular condyle which varied in thickness (Fig 4d).…”
Section: Histopathological Findingssupporting
confidence: 55%
See 2 more Smart Citations
“…The hyaline cartilage contained many hypertrophied chondrocytes and relatively small foci of necrosis. The deep layers of the hyaline cartilage were undergoing endochondral ossification, as expected in a horse less than 2 years old (Smyth et al, 2019). There was a relatively large depression in the lateral aspect of the articular surface of the mandibular condyle which varied in thickness (Fig 4d).…”
Section: Histopathological Findingssupporting
confidence: 55%
“…Multiple osteochondral fragmentswithin the depression of the articular surface of the mandibular condyle and the The intra-articular disc contained at least one focus of chondro-osseous metaplasia and three foci of woven and lamellar trabecular bone, which is commonly found in the intra-articular disc of much older horses (Smyth et al, 2019).…”
Section: Histopathological Findingsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, such models are often referred to as naturally occurring models. Studies have shown that STR/Ort ( Kumagai et al, 2015 ; Yamashita-Futani et al, 2021 ), STR/IN ( Dreessen and Halata, 1990 ), SAMP8 ( Ishizuka et al, 2014 ), C57BL/6S ( Fukuoka et al, 1993 ), C57BL/6J ( Cui et al, 2020 ), C57BL/6NCrSlc ( Ukita et al, 2020 ), ICR ( Silbermann and Livne, 1979 ; Livne and Silbermann, 1986 ) mice, Dunkin-Hartley guinea pigs ( Wu et al, 2016 ), and horses ( Smyth et al, 2019 ) all manifest OA-like lesions with increasing age, among which multiple subtypes of SAM mice can develop OA-like lesions in TMJ ( Chen et al, 1989 ) ( Table 5 ). Yamashita-Futani et al (2021) found in STR/Ort mice that the production of elastin-digested peptides was related to the upregulation of pro-inflammatory mediators, such as IL-6 and MMP-12.…”
Section: Classification Of Animal Models In Temporomandibular Joint O...mentioning
confidence: 99%
“…Osteoarthritis (OA) stands out as the most prevalent degenerative disease affecting the temporomandibular joint (TMJ), manifesting spontaneously in humans [ 1 ] and various animal species, such as mice [ 2 , 3 ], guinea pigs [ 4 ], and horses [ 5 , 6 , 7 , 8 , 9 , 10 ]. TMJ OA is characterized as a chronic disease marked by degenerative alterations in cartilage, accompanied by reparative processes in the surrounding tissues [ 1 , 11 , 12 , 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%